2006
DOI: 10.4315/0362-028x-69.1.6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Survival in Feces and Water of Escherichia coli O157:H7 Grown under Laboratory Conditions or Obtained from Cattle Feces

Abstract: Escherichia coli O157:H7 is an important foodborne pathogen that can cause hemorrhagic colitis and hemolytic uremic syndrome. Cattle feces and fecally contaminated water are important in the transmission of this organism on the farm. In this study, the survival of E. coli O157:H7 in feces and water was compared following passage through the animal digestive tract or preparation in the laboratory. Feces were collected from steers before and after oral inoculation with a marked strain of E. coli O157:H7. Fecal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…Kudva et al (33) reported no differences in survival in bovine manure and manure slurry between toxin-positive (Stx1 ϩ Stx2 ϩ ) and toxin-negative (Stx1 Ϫ Stx2 Ϫ ) E. coli O157:H7 strains. In addition, survival in manure of E. coli O157:H7 that passed the intestinal tract of cattle was not different from the survival of the same strain directly inoculated into the manure (48). Bacteria were stored at Ϫ80°C and checked for viability prior to use by growing on Luria-Bertani medium supplemented with ampicillin (50 g ml Ϫ1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Kudva et al (33) reported no differences in survival in bovine manure and manure slurry between toxin-positive (Stx1 ϩ Stx2 ϩ ) and toxin-negative (Stx1 Ϫ Stx2 Ϫ ) E. coli O157:H7 strains. In addition, survival in manure of E. coli O157:H7 that passed the intestinal tract of cattle was not different from the survival of the same strain directly inoculated into the manure (48). Bacteria were stored at Ϫ80°C and checked for viability prior to use by growing on Luria-Bertani medium supplemented with ampicillin (50 g ml Ϫ1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that E. coli O157:H7 can survive in water for up to 109 days (Scott et al, 2006). Water supplies contaminated with livestock effl uent have been implicated in a number of outbreaks (Locking et al, 2006).…”
Section: Prevention Of Ingestion Of the Pathogenmentioning
confidence: 99%
“…In addition to temperature, the indigenous microflora (93), scarcity of nutrients (96), and protozoan predations also influence survival. Recent passage of VTEC through the bovine gastrointestinal tract may enhance survival of O157 in water (97).…”
Section: Vtec In Watermentioning
confidence: 99%
“…However, it should be noted that not all strains belonging to these serogroups will cause severe illness and that other non-O157 VTEC serogroups also cause illness. Pathogenic VTEC strains are categorized as enterohemorrhagic E. coli, and usually in these strains, a large outer membrane protein (94)(95)(96)(97) called intimin mediates the intimate contact between the bacterium and the enterocyte cytoplasmic membrane (attachment) and the destruction of the enterocyte microvilli (effacement). The genetic determinants for this (eae, tir, esc, and sep genes) are grouped together on the chromosome, forming a pathogenicity island called LEE, for locus of enterocyte effacement (7).…”
Section: Human Pathogenic Vtecmentioning
confidence: 99%